Analisis Hukum Zakat di Indonesia: Studi terhadap Perundang-undangan dan Fatwa Majelis Ulama Indonesia - Nur Irmandi; Nur Hafizhatul Khairi; Syukron Suwardi; Ending Solehudin (IQTISHOD: Jurnal Pemikiran dan Hukum Ekonomi Syariah, 2025)
This article discusses the management of zakat in Indonesia by referring to the applicable laws and regulations, namely Law No. 38/1999 on Zakat Management, Law No. 23/2011 on Zakat Management, and Government Regulation No. 14/2014. Through a qualitative analysis approach, this article identifies the development of zakat policy in Indonesia and the contribution of the Fatwa of the Indonesian Ulema Council (MUI) to the implementation of more effective zakat management. The results of the study show that despite progress in zakat regulation, challenges related to transparency, accountability, and resource management are still issues that need further attention